Transport and programmed release of nanoscale cargo from cells by using NETosis. Issue 16 (14th April 2020) - Meyer, Daniel; Telele, Saba; Zelená, Anna; Gillen, Alice J.; Antonucci, Alessandra; Neubert, Elsa; Nißler, Robert; Mann, Florian A.; Erpenbeck, Luise; Boghossian, Ardemis A.; Köster, Sarah; Kruss, Sebastian
Abstract : Immune cells take up nanoscale materials and can be programmed to release it again, which has important implications for understanding cellular functions, biocompatibility as well as biomedical applications. Abstract : Cells can take up nanoscale materials, which has important implications for understanding cellular functions, biocompatibility as well as biomedical applications. Controlled uptake, transport and triggered release of nanoscale cargo is one of the great challenges in biomedical applications of nanomaterials. Here, we study how human immune cells (neutrophilic granulocytes, neutrophils) take up nanomaterials and program them to release this cargo after a certain time period. For this purpose, we let neutrophils phagocytose DNA-functionalized single-walled carbon nanotubes (SWCNTs) in vitro that fluoresce in the near infrared (980 nm) and serve as sensors for small molecules. Cells still migrate, follow chemical gradients and respond to inflammatory signals after uptake of the cargo. To program release, we make use of neutrophil extracellular trap formation (NETosis), a novel cell death mechanism that leads to chromatin swelling, subsequent rupture of the cellular membrane and release of the cell's whole content. By using the process of NETosis, we can program the time point of cargo release via the initial concentration of stimuli such as phorbol 12-myristate-13-acetate (PMA) or lipopolysaccharide (LPS). At intermediate stimulation, cells continue to migrate, follow gradients and surface cues for around 30 minutes and up to several hundred micrometers until they stop and release the SWCNTs. The transported and released SWCNT sensors are still functional as shown by subsequent detection of the neurotransmitter dopamine and reactive oxygen species (H2 O2 ). In summary, we hijack a biological process (NETosis) and demonstrate how neutrophils transport and release functional nanomaterials.